Repurposing Mebendazole as a Replacement for Vincristine for the Treatment of Brain Tumors - Michelle De Witt; Alexander Gamble; Derek Hanson; Daniel Markowitz; Caitlin Powell; Saleh Al Dimassi; Mark Atlas; John Boockvar; Rosamaria Ruggieri; Marc Symons (BMC, 2017)
Abstract The microtubule inhibitor vincristine is currently used to treat a variety of brain tumors, including low-grade glioma and anaplastic oligodendroglioma. Vincristine, however, does not penetrate well into brain tumor tissue, and moreover, it displays dose-limiting toxicities, including peripheral neuropathy. Mebendazole, a Food and Drug Administration-approved anthelmintic drug with a favorable safety profile, has recently been shown to display strong therapeutic efficacy in animal models of both glioma and medulloblastoma. Importantly, appropriate formulations of mebendazole yield therapeutically effective concentrations in the brain. Mebendazole has been shown to inhibit microtubule formation, but it is not known whether its potency against tumor cells is mediated by this inhibitory effect. To investigate this, we examined the effects of mebendazole on GL261 glioblastoma cell viability, microtubule polymerization and metaphase arrest, and found that the effective concentrations to inhibit these functions are very similar. In addition, using mebendazole as a seed for the National Cancer Institute (NCI) COMPARE program revealed that the top-scoring drugs were highly enriched in microtubule-targeting drugs. Taken together, these results indicate that the cell toxicity of mebendazole is indeed caused by inhibiting microtubule formation. We also compared the therapeutic efficacy of mebendazole and vincristine against GL261 orthotopic tumors. We found that mebendazole showed a significant increase in animal survival time, whereas vincristine, even at a dose close to its maximum tolerated dose, failed to show any efficacy. In conclusion, our results strongly support the clinical use of mebendazole as a replacement for vincristine for the treatment of brain tumors.